2018
DOI: 10.1111/medu.13728
|View full text |Cite
|
Sign up to set email alerts
|

Keeping mum in clinical supervision: private thoughts and public judgements

Abstract: CONTEXT The seemingly obvious claim that people prefer to keep mum about undesirable messagestermed 'the MUM effect'was initially reported in the psychology literature in the 1970s. More recently, it has been discussed in contexts including performance appraisals and the reporting of unsuccessful projects in workplace settings, but only sparsely in educational ones. We wished to review the published literature on the MUM effect in order to understand the implications for clinical assessment.METHODS We performe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
44
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(49 citation statements)
references
References 63 publications
2
44
0
3
Order By: Relevance
“…To summarise, in addition to the actions to ameliorate the MUM effect described by Scarff et al, 2 we highlight the significance of the characteristics of the recipient and of the social cues in the clinical training setting. We propose that a setting that deemphasises competition with others and that accepts making mistakes as part of the learning process may stimulate a learning goal orientation, which may subsequently reduce unpleasant feelings towards negative messages for both the recipient and communicator.…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…To summarise, in addition to the actions to ameliorate the MUM effect described by Scarff et al, 2 we highlight the significance of the characteristics of the recipient and of the social cues in the clinical training setting. We propose that a setting that deemphasises competition with others and that accepts making mistakes as part of the learning process may stimulate a learning goal orientation, which may subsequently reduce unpleasant feelings towards negative messages for both the recipient and communicator.…”
mentioning
confidence: 99%
“…Referring to this struggle, Scarff et al turn to the literature on the MUM effect (keeping Mum about Unpleasant Messages) in this issue of Medical Education. 2 The MUM effect indicates that individuals have more difficulty in delivering negative than positive messages, which often leads to avoiding or sugar-coating the negative information. Our own research and that of others suggested that people agree more on what is considered undesirable, as opposed to desirable, because undesirable actions always lead to negative outcomes.…”
mentioning
confidence: 99%
See 3 more Smart Citations